MEMETAKAN LINGKUP INFORMASI PENGHIDUPAN ORANG MISKIN PEDESAAN - Priyo Subekti; Pawit M. Yusup; Tine Silvana Rachmawati (Universitas Padjadjaran, 2013)
This study aims to map out the scope of information the livelihoods of the rural poor, which include: the type of major need, the search pattern related information specific type of job, the variety of information livelihoods are looking for, the relationship between the rural poor, sources of information, channel information, and the nature of sources and channels of information in question. By using qualitative methods, especially the tradition of phenomenology of Schutz, the result that: (1) the type of the primary needs of the rural poor consist of food, clothing, shelter, health, and education are very simple; (2) a variety of livelihood information sought by the rural poor who work odd nature, derived from the interpersonal sources that are informal, with a limited scope, ie, neighbors, relatives, customers, and the kind of fellow workers; (3) the source and drain are derived from official media and technology based, hardly ever used; and (4) The formal elements that come from the government side, barely touched the interests of the rural poor.Penelitian ini bertujuan untuk memetakan lingkup informasi penghidupan orang miskin pedesaan, yang meliputi: jenis kebutuhan utama, pola pencarian informasi terkait jenis pekerjaan spesifik, ragam informasi penghidupan yang dicari, hubungan antar orang miskin pedesaan, sumber-sumber informasi, saluran informasi, dan sifat dari sumber dan saluran informasi dimaksud. Dengan menggunakan metode kualitatif khususnya tradisi fenomenologi dari Schutz, diperoleh hasil bahwa: (1) jenis kebutuhan utama orang miskin pedesaan terdiri atas kebutuhan pangan, sandang, papan, kesehatan, dan pendidikan yang sangat sederhana; (2) beragam informasi penghidupan yang dicari oleh orang miskin pedesaan yang sifat pekerjaannya serabutan, berasal dari sumber orang secara interpersonal yang bersifat informal, dengan lingkup yang terbatas, yakni tetangga, kerabat, pelanggan, dan sesama pekerja sejenis; (3) sumber dan saluran yang berasal dari media resmi dan yang berbasis teknologi, hampir tidak pernah digunakan; dan (4) unsur-unsur formal yang datangnya dari sisi pemerintah, hampir tidak menyentuh kepentingan orang-orang miskin pedesaan.